CNC PROGRAM AND PROGRAMMING OF CNC MACHINE - Maya Fatriyana (Journal of Mechanical Science and Engineering, 2020)
CNC Programming (Computer Numerical Control Programming) is the art of programming CNC machines to make parts. An NC Program consists of a sequence of instructions that control the motion and automatic sequences of an NC Machine. In general sense, the term NC programming refers to the creation of control data for machining work-pieces on NC and CNC machines. The development of CNC systems has progressed as a result of the rapidly improving capabilities, coupled with falling prices, of small computers, a combination that makes the standard computer an attractive component of NC systems. NC programming has a decisive influence on the cost effectiveness and profitability of NC manufacturing. The selection of a programming system is essentially guided by the need for software that is suitable for the application at hand, readily available, and as universally applicable as possible.